Neonatal gut microbiota succession in mice mapped over time, site, injury and single immunoglobulin interleukin-1 related receptor genotype - Shahid Umar; Wei Yu; Hao Xuan; Ishfaq Ahmed; Cuncong Zhong; Michael Morowitz; Mathew Brian Rogers; Mark Ivan Attard; Venkatesh Sampath (iScience)
Summary: Microbial succession during postnatal gut development in mice is likely impacted by site of sampling, time, intestinal injury, and host genetics. We investigated this in wild-type and Sigirr transgenic mice that encode the p.Y168X mutation identified in a neonate with necrotizing enterocolitis (NEC). Temporal profiling of the ileal and colonic microbiome after birth to weaning revealed a clear pattern of progression from a less diverse, Proteobacteria/Escherichia_Shigella dominant community to a more diverse, Firmicutes/Bacteroidetes dominant community. Formula milk feeding, a risk factor for necrotizing enterocolitis, decreased Firmicutes and increased Proteobacteria leading to enrichment of bacterial genes denoting exaggerated glycolysis and increased production of acetate and lactate. Sigirr transgenic mice exhibited modest baseline differences in microbiota composition but exaggerated formula feeding-induced dysbiosis, mucosal inflammation, and villus injury. Postnatal intestinal microbiota succession in mice resembles human neonates and is shaped by developmental maturity, ileal vs. colonic sampling, formula feeding, and Sigirr genotype.